2014
DOI: 10.1080/13691058.2014.891049
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary evaluation of a behavioural HIV-prevention programme for teenage girls of Latino descent in the USA

Abstract: National data suggests that teenage girls of Latino descent in the USA are disproportionately affected by HIV with the rate of new infections being approximately 4 times higher compared to White women of comparable age (Centers for Disease Control and Prevention 2013). This paper highlights the need for an effective single-sex HIV prevention program for teenage girls of Latino descent and describes the development and preliminary evaluation of Chicas Healing, Informing, Living and Empowering (CHILE), a cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
10
0
2
Order By: Relevance
“…A series of clinic-based sexual health interventions developed by DiClemente and colleagues have emphasized issues of gender, empowerment and healthy relationships, with evidence supporting their impact on both psychosocial mediators and behavioral outcomes for sexually active African American adolescent girls [ 30 , 46 ]. A similar intervention for Hispanic adolescent girls is under development [ 47 ]. The preliminary findings from the present SEI evaluation trial lend further support to the potential of rights-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinic-based sexual health interventions developed by DiClemente and colleagues have emphasized issues of gender, empowerment and healthy relationships, with evidence supporting their impact on both psychosocial mediators and behavioral outcomes for sexually active African American adolescent girls [ 30 , 46 ]. A similar intervention for Hispanic adolescent girls is under development [ 47 ]. The preliminary findings from the present SEI evaluation trial lend further support to the potential of rights-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Although culturally-focused interventions for Latino youth in the USA are rare, programmes that incorporate cultural sensitivity have been endorsed by young people (Davidson et al 2014) and found to reduce risky behaviours and increase testing rates (Añez et al 2008;Crepaz et al 2007;Fisher et al 2011). Interventions to promote HIV testing among Latino young people would be likely to benefit from a better understanding of the influence of culture on testing behaviours.…”
mentioning
confidence: 97%
“…Therefore, current tobacco use prevention efforts mainly implemented through public schools are likely to be applicable to Latinx youth with varying personal and family migration histories. Nonetheless, there may be benefits to certain cultural adaptations of generally applicable prevention programs, such as those used for HIV-prevention and alcohol abuse programs among Latinxs [ 34 , 35 ]. Our findings raise questions about the immigrant paradox as it applies to tobacco use for Latinx adolescents.…”
Section: Discussionmentioning
confidence: 99%